New species of Rhagoletotrypeta (Diptera: Tephritidae) from the Dominican Republic and southern Brazil and Paraguay - Norrbom, Allen L.; Savaris, Marcoandre; Marinoni, Luciane (Zootaxa, 2016)
Rhagoletotrypeta chapecensis Norrbom & Savaris, new species, and R. gelabertae Norrbom & Savaris, new species, are described and illustrated from specimens from southern Brazil (Paraná, Santa Catarina) and Paraguay, and from the Dominican Republic, respectively. The larvae of R. chapecensis develop in fruits of Celtis iguanaea (Jacq.) Sarg. (Ulmaceae). A key to the species of the xanthogastra species group is provided.